(3QSGdI eMeO GdecdGJi Edi eMeO Hf GdbGSe Hf GdbGVi hGdQO YdjgGs - (3eMeO Hf CMeO Hf eMeO Hf CMeO, CHh YHO Gddg GdecdGJj; jbGd dg GdecdGJj GdGcHQ,J (B1041 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hMOg hLOJ HNW Gdabjg GdYdGeI SjOi GdMGL eMeO Hf GdbGSe s
(3BNQgG (B:s
(3hdce GdaVd hGdGZVGA hQGdJLGhR hGdSdGe CNhce GdecdGJi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B109 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B318s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B37 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B- (3GdQHGW (B((3O (B487) s
Keywords: (3GdCOHs